Ultrahigh‐Gain Organic Electrochemical Transistor Chemosensors Based on Self‐Curled Nanomembranes. Issue 29 (1st June 2021) - Ferro, Letícia M. M.; Merces, Leandro; de Camargo, Davi H. S.; Bof Bufon, Carlos C.
Abstract: Organic electrochemical transistors (OECTs) are technologically relevant devices presenting high susceptibility to physical stimulus, chemical functionalization, and shape changes—jointly to versatility and low production costs. The OECT capability of liquid‐gating addresses both electrochemical sensing and signal amplification within a single integrated device unit. However, given the organic semiconductor time‐consuming doping process and their usual low field‐effect mobility, OECTs are frequently considered low‐end category devices. Toward high‐performance OECTs, microtubular electrochemical devices based on strain‐engineering are presented here by taking advantage of the exclusive shape features of self‐curled nanomembranes. Such novel OECTs outperform the state‐of‐the‐art organic liquid‐gated transistors, reaching lower operating voltage, improved ion doping, and a signal amplification with a >10 4  intrinsic gain. The multipurpose OECT concept is validated with different electrolytes and distinct nanometer‐thick molecular films, namely, phthalocyanine and thiophene derivatives. The OECTs are also applied as transducers to detect a biomarker related to neurological diseases, the neurotransmitter dopamine. The self‐curled OECTs update the premises of electrochemical energy conversion in liquid‐gated transistors, yielding a substantial performance improvement and new chemical sensing capabilities within picoliter sampling volumes. Abstract : Organic electrochemical transistors (OECTs) have attracted growing interest due to their physical, chemical, and mechanical versatility. Simultaneously, strain‐engineered nanomembranes are well recognized to allow integration and property tailorability to numerous electronic and electrochemical miniaturized systems. By employing self‐curled nanomembranes to advance the current liquid‐gated transistor technology, unique characteristics arise in a pioneering ultrahigh‐gain OECT platform.